Protosclerogibba australis gen. et sp. nov., new genus and species of sclerogibbid wasps (Hymenoptera: Sclerogibbidae) from South Africa - Olmi, Massimo; Marletta, Alessandro; Guglielmino, Adalgisa; Speranza, Stefano (Zootaxa, 2016)
Protosclerogibba australis Olmi, Marletta, Guglielmino & Speranza, gen. et sp. nov. is described and illustrated from specimens collected in Kimberley (Northern Cape Province, South Africa). The female of the new taxon is the first micropterous sclerogibbid. Females of other extant Sclerogibbidae are always apterous, whereas fossil females can be apterous or macropterous.